A comparative study of the experiences of specialist and nonspecialist teachers of physical education in elementary schools - Coles, Ellis S., 1962- (1995)
Thesis (M.P.E.)--Memorial University of Newfoundland, 1995. Physical Education and Athletics Bibliography: leaves 129-134.